2011
DOI: 10.1089/jpm.2011.0106
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Medicine Physicians' Perspectives of Providing Palliative Care in an Emergency Department

Abstract: This study describes emergency physicians' perspectives on the challenges and benefits to providing palliative care in an academic, urban, public hospital in Los Angeles. Participants underwent a semi-structured interview on their training and experiences related to palliative care, perceptions of providing palliative care, and their recommendations for education and training in this area. Overall, respondents felt that palliative care is not prioritized appropriately, leading patients to be unaware of their o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
94
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(100 citation statements)
references
References 13 publications
4
94
1
1
Order By: Relevance
“…It has been reported that PC can be improved in parallel with training and, particularly lack of training related to communication causes problems (6). In another study, emergency service physicians claimed that their emergency medicine knowledge and skills are not adequate for PC, and they should be given additional training on this issue (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that PC can be improved in parallel with training and, particularly lack of training related to communication causes problems (6). In another study, emergency service physicians claimed that their emergency medicine knowledge and skills are not adequate for PC, and they should be given additional training on this issue (13).…”
Section: Discussionmentioning
confidence: 99%
“…These two different perspectives are on the basis of the possible problems of palliative care patients in the emergency services. Although there is a rapid circulation of patients in emergency services, ED physicians can provide necessary care to this special patient group with sufficient knowledge and skills (1,6). Despite the differences in health care systems of the countries and differences in the emergency service approaches depending on the hospital based palliative care teams and services, it is quite important to diagnose these patient groups early in ED to properly apply symptomatic approaches and to provide guidance afterwards.…”
Section: Introductionmentioning
confidence: 99%
“…Management of palliative care emergencies is focused on the symptoms, rather than the primary disease, and also includes the emotional, physical, and social aspects of the patients, caregivers, and families, which are different from those in other emergencies (3). The ED has a unique approach on its own and has started drawing much attention in the literature, particularly by ER physicians, with an increasing number of admissions of palliative care patients to the ED around the world (7,8). There are some radical approaches to ED care and also limitations due the physical conditions, such as problems caused by the size, crowdedness, loud environment, and limited circumstances in many cases (8).…”
Section: Introductionmentioning
confidence: 99%
“…The ED has a unique approach on its own and has started drawing much attention in the literature, particularly by ER physicians, with an increasing number of admissions of palliative care patients to the ED around the world (7,8). There are some radical approaches to ED care and also limitations due the physical conditions, such as problems caused by the size, crowdedness, loud environment, and limited circumstances in many cases (8). Emergency physicians who work in a hospital with no palliative care center or team have to be qualified in palliative care skills in order to provide most accurate approaches to palliative care patients and families.…”
Section: Introductionmentioning
confidence: 99%
“…5,52,53 Moreover, many ED providers erroneously believe that their patients' PC needs are already being met in other clinical settings. 54,55 ED practitioners have also cited lack of 24-hour coverage by consultants as a major barrier to PC consultation.…”
mentioning
confidence: 99%